1997
DOI: 10.1107/s0108768197008240
|View full text |Cite
|
Sign up to set email alerts
|

New Bond-Valence Sum Model

Abstract: A new expression is devised empirically to accommodate zero and some negative oxidation states in the bondvalence sum approach. The method is worked out in detail for a number of homoleptic copper and nickel complexes of various coordinating atoms in several oxidation states of the metals. An implication of the expression is a linear variation between 1/req and 1/rax in octahedral MX 6 moieties, where req and tax are, respectively, the average equatorial and axial bond lengths. This is verified in Cu2+X6 chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…(3) Since the coordination number of the metal ion changes so much with the change in the oxidation state, the peak-to-peak separation in Figure 5 is quite large (0.17 V). The reasons for assuming that the Cu II species in Equation (3) is four-coordinate are as follows: (i) While a number of structurally characterised copper(i) complexes having a Cu I N 2 core are known, [10] no one has ever observed a quasi-reversible cyclic voltammogram for such a core (an irreversible voltammogram with possible characteristics of adsorption is expected for a Cu I N 2 core). (ii) No example of a two-coordinate copper(ii) complex is known in the literature; hence, the copper(ii) species in Equation (3) cannot have a Cu II N 2 core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Since the coordination number of the metal ion changes so much with the change in the oxidation state, the peak-to-peak separation in Figure 5 is quite large (0.17 V). The reasons for assuming that the Cu II species in Equation (3) is four-coordinate are as follows: (i) While a number of structurally characterised copper(i) complexes having a Cu I N 2 core are known, [10] no one has ever observed a quasi-reversible cyclic voltammogram for such a core (an irreversible voltammogram with possible characteristics of adsorption is expected for a Cu I N 2 core). (ii) No example of a two-coordinate copper(ii) complex is known in the literature; hence, the copper(ii) species in Equation (3) cannot have a Cu II N 2 core.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] For example, in azurin − a blue copper-containing protein − there is a peptide carbonyl O atom in close proximity to the metal ion [mean Cu I -O distance = 3.22 Å; mean Cu II -O distance = 3.13 Å], [9] although it is doubtful whether this O atom is bonded to the copper atom [ in azurin. [10] Thus, the possibility of a copper(i)-keto oxygen bond is of biological relevance as well. Recently, we have undertaken a project to study the chemistry of this bond, and here we make the first report of our efforts by describing some properties of a homoleptic copper(i) complex of 2-acetylpyridine (ACPY) containing copper(i)-keto oxygen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In order to assign the oxidation state of complex 1 , we have taken recourse to the calculation based on bond valence sum (BVS) method . According to the reported method, the BVS values of copper centers in complex 1 were 1.85 for Cu1 and 1.81 for Cu2 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatives to Eq. (5) for describing the bond valence-bond length correlation have been proposed by Ziolkowski [42], Naskar et al [43], Valach [44], and Mohri [45], but these have not found widespread favor. In a seminal paper in 2001, Adams [46] showed that increasing the coordination number around an atom, by increasing the bond cut-off distance, causes an increase in the value of b and a decrease in that of R 0 , the values stabilizng only after the cut-off length reaches around 5 Å .…”
Section: The Origin and Development Of The Bond Valence Theorymentioning
confidence: 99%